2013
DOI: 10.1101/gad.229062.113
|View full text |Cite
|
Sign up to set email alerts
|

α-Catenin interacts with APC to regulate β-catenin proteolysis and transcriptional repression of Wnt target genes

Abstract: Mutation of the adenomatous polyposis coli (APC) tumor suppressor stabilizes b-catenin and aberrantly reactivates Wnt/b-catenin target genes in colon cancer. APC mutants in cancer frequently lack the conserved catenin inhibitory domain (CID), which is essential for b-catenin proteolysis. Here we show that the APC CID interacts with a-catenin, a Hippo signaling regulator and heterodimeric partner of b-catenin at cell:cell adherens junctions. Importantly, a-catenin promotes b-catenin ubiquitylation and proteolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 49 publications
5
91
0
4
Order By: Relevance
“…Intriguingly, loss of APC, a component of the β-catenin destruction complex and actin-nucleating factor (Moseley et al, 2007;Okada et al, 2010), has also been found to increase DNA damage and genomic instability (Aoki et al, 2007;Fodde et al, 2001a;Meniel et al, 2015). APC has been shown to translocate into the nucleus, bind both α-and β-catenin and inhibit transcription (Choi et al, 2013), which is reminiscent of the role of nuclear α-catenin (Daugherty et al, 2014;McCrea and Gottardi, 2016). Furthermore, nuclear APC is directly recruited to sites of DNA damage repair (Kouzmenko et al, 2008) and has been implicated in base excision repair (Narayan and Sharma, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, loss of APC, a component of the β-catenin destruction complex and actin-nucleating factor (Moseley et al, 2007;Okada et al, 2010), has also been found to increase DNA damage and genomic instability (Aoki et al, 2007;Fodde et al, 2001a;Meniel et al, 2015). APC has been shown to translocate into the nucleus, bind both α-and β-catenin and inhibit transcription (Choi et al, 2013), which is reminiscent of the role of nuclear α-catenin (Daugherty et al, 2014;McCrea and Gottardi, 2016). Furthermore, nuclear APC is directly recruited to sites of DNA damage repair (Kouzmenko et al, 2008) and has been implicated in base excision repair (Narayan and Sharma, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have previously shown that αE-catenin (also known as CTNNA1; originally identified in epithelia, but now recognized as the most ubiquitously expressed α-catenin isoform, and thus hereafter referred to as α-catenin) can accumulate in the nucleus in a WNT/β-catenin-dependent manner (Choi et al, 2013;Daugherty et al, 2014;Giannini et al, 2000;Merdek et al, 2004). Nuclear α-catenin attenuates transcription of WNT pathwayresponsive genes via β-catenin.…”
Section: Introductionmentioning
confidence: 99%
“…and degradation by stabilizing its binding to APC. 37 On the other hand, the interaction of α-catenin with APC leads to nuclear translocation of APC and formation of a protein complex consisting of APC:α-catenin:β-catenin and the CtBP:CoREST:LSD1 histone H3K4 demethylase, which inhibits the transcription of Wnt target genes. 37 Interestingly, tyrosine phosphorylation of α-catenin at Y177 disrupts its interaction with APC but not β-catenin and releases the transcriptional repression of Wnt target genes.…”
Section: α-Catenin Signaling In Cancermentioning
confidence: 99%
“…37 On the other hand, the interaction of α-catenin with APC leads to nuclear translocation of APC and formation of a protein complex consisting of APC:α-catenin:β-catenin and the CtBP:CoREST:LSD1 histone H3K4 demethylase, which inhibits the transcription of Wnt target genes. 37 Interestingly, tyrosine phosphorylation of α-catenin at Y177 disrupts its interaction with APC but not β-catenin and releases the transcriptional repression of Wnt target genes. 37 These experiments demonstrate that α-catenin can suppress Wnt signaling by promoting β-catenin degradation, by hindering nuclear translocation of β-catenin, by preventing formation of the β-catenin-TCF-DNA complex, or by recruiting APC to the β-catenin-TCF complex (Fig.…”
Section: α-Catenin Signaling In Cancermentioning
confidence: 99%
See 1 more Smart Citation